Pentingnya Kasih Sayang Orang Tua untuk Mendukung Tumbuh Kembang Anak Usia Dini yang Berkebutuhan Khusus - Witri Islaura Wulandari (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
This article discusses the crucial role of parental love and support in promoting the growth and development of young children with special needs. Children with special needs require a more specific and consistent approach to supporting their physical, emotional, and social development. Parents play a central role in providing a safe, comfortable, and loving environment that can stimulate the abilities and skills of the child. Through an inspirational story of a mother who successfully supports her child with special needs to achieve academic success, this article explores how intensive parental attention can have a significant positive impact. Parental love not only creates a harmonious relationship but also fosters self-confidence in the child, enhances adaptability, and strengthens social skills needed for independence. Research shows that children with special needs who receive full parental support tend to experience more optimal development compared to those who do not receive the same support. This article highlights the importance of educating parents to understand the specific conditions and needs of children with special needs, as well as to apply appropriate parenting methods to support the child's future success.